ОГРАНИЧЕНИЕ СВОБОДЫ ВЫРАЖЕНИЯ МНЕНИЯ В ЦЕЛЯХ НАЦИОНАЛЬНОЙ БЕЗОПАСНОСТИ УКРАИНЫ: КОНСТИТУЦИОННО-ПРАВОВОЙ АНАЛИЗ - Васильченко, Оксана (SUPREMANCE OF LAW, 2017)
Ukraine has obliged to abide by international law and international agreements, in particular with regard to the protection of human rights in respect of freedom of expression, conscience, thought and religionE and “confirmed” its choice during dramatic events of2013-2014 in the course of the Revolution of Dignity. Freedom of speech should be considered as a component of a democratic political culture in the context of social self-sufficiency. Freedom of speech in the form in which it is presented in the Article 10 of the European Convention on Human Rights, has numerous exceptions, which are however subject to specific restrictions elaborated in the course of practice of states and international organisations. Ukraine formally derogated from the International Covenant on Civil and Political Rights and the European Convention on Human Rights due to the situation created by the agression of the Russian Federation. To this end, relevant laws were adopted, particularly, on the state of necessity in the state, that, however, has not been introduced in the country. Ukraine should be cautious when enforcing the respective legislation, including the restitution of the freedom of expression. The OSCE and other non-governmental organisations monitor the situation with the freedom of media and speech in Ukraine. Thus, it is a challenge for Ukraine to ensure its national security and guarantee the exercise of human rights and freedoms.